SUBALTERNITAS DAN PERGULATAN IDENTITAS WARIA - Haidar Sofi Al Kharis,; Putri Ayu Pratna Paramita,; Riris Puspitasari, (Jurnal Bintang Pendidikan Indonesia, 2023)
Waria are one of many different types of sexual intermediaries, including homosexuals and hermaphrodites who occupy the spectrum between pure men and pure women (Susan Stryker, 2008). From this quote, it can be understood that waria is like one who occupies a middle position between the concepts of men and women. The most obvious thing that distinguishes waria from men and women is the way they look that is not in accordance with the general sex that has been assigned to them since birth. Those who are biologically born male, in fact they (waria) look the opposite and resemble women. Waria often receive bad treatment from society such as discrimination, mental and physical violence and other actions that are contrary to morality. On May 2, 2022 waria who are members of the wagayo organization (Waria and gay organization) in Jember, East Java took action to commemorate national education day. From the attached news, the waria provide information that waria also want to get the same place as people in general in the world of education. This is enough to explain the existence of discrimination against transgender women even in the world of education which results in many transgender people being forced to drop out of school because they cannot stand ridicule from both friends and educators at their schools. This has implications for the cause of the low human resources of waria.